Investigation of Nanosized Crystalline Form to Improve the Oral Bioavailability of Poorly Water Soluble Cilostazol - Xiaoqing Miao; Changshan Sun; Tongying Jiang; Li Zheng; Tianyi Wang; Siling Wang (Frontiers Media S.A., 2011)
Purpose: The aim of this study was to develop cilostazol (CLT) nanocrystals intended to improve its dissolution rate and enhance its bioavailability. Methods: In this study, CLT nanosuspension was prepared by the anti-solvent and high-pressure homogenization method. The effects of the production parameters, such as the stabilizer concentration, pressure and number of cycles, were investigated. Characterization of the product was performed by scanning electron microscopy (SEM), Nitrogen adsorption, differential scanning calorimetry (DSC), X-ray powder diffraction analysis (XRPD), X-ray Photoelectron Spectroscopy (XPS), particle size analysis and dissolution testing. Additionally, the comparison studies of oral bioavailability in beagle dogs of three type tables were performed. Results: The images of SEM showed a spherical smooth CLT powder, and Nitrogen adsorption test revealed spray dried powder were porous with high BET surface area compared with that of raw CLT. DSC and XRPD results demonstrated that the combination of preferred polymorph B and C of CLT were prepared successfully, the saturation solubility of the nanosized crystalline powder is about 5 fold greater than that of raw CLT, and the dissolution rate was enhanced 4 fold than that of raw CLT. The Cmax and AUC0-48h of CLT nanosized crystalline tablets were 2.1 fold and 1.9 fold, and 3.0 fold and 2.3 fold compared with those of the nanosized tablets and commercial tablets, respectively. Conclusion: The anti-solvent-high-pressure homogenization technique was employed successfully to produce cilostazol nanosuspensions. The bioavailability of CLT tablets prepared using spray dried nanosized crystalline powder after oral administration to dogs was markedly increased compared with that produced by nanosized tablets and commercial tablets, because of its greater dissolution rate owing to its transition of the crystalline state to form C and form B, reduced particle size and porous structure with increased surface area. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.